A qualitative study of legal and social justice needs for people with aphasia. (December 2014) - Morris, Karen; Ferguson, Alison; Worrall, Linda
Abstract This paper presents an exploratory investigation of situations in which people with aphasia may be vulnerable to legal and access to justice issues. The study used a qualitative descriptive approach to analyse 167 de-identified transcriptions of previously collected interviews, with 50 participants with mild-to-severe aphasia following stroke, 48 family members, and their treating speech-language pathologists. Situations experienced by people with aphasia and their family members were coded using key-word searches based on the previously published framework developed by Ellison and colleagues to describe situations of vulnerability to legal and access to justice needs for older people. Health and financial and consumer situations were most frequently identified in the data. Additionally, there were a number of situations found specifically relating to people with aphasia involving their signatures and credit card use. Instances of discrimination and abuse were also identified, and, although infrequent, these issues point to the profound impact of aphasia on the ability to complain and, hence, to ensure rights to care are upheld. The findings of this study are consistent with previous research in suggesting that legal and access to justice needs are an important issue for people with aphasia and their families.